Effectiveness Of Training Cost Method Of Using Serial And Parallel To Increase Power And Leg Muscle Strength, Muscles Back, Stomach Muscle - Muhammad Salabi; Day Setijono; Soetanto Hartono (JUPE : Jurnal Pendidikan Mandala, 2018)
This study aims to determine the effect of weight training using serial and parallel methods in improving the power and strength of leg muscles, back muscles, abdominal muscles. Subjects in the study were students of Teachers' Training FPOK Mataram academic year 2014/2015 which were both undergoing training load with two training methods. This study uses a quantitative approach using experimental method with factorial design. The research instrument to measure the strength of the back muscles and leg muscle strength using a dynamometer leg,meter the leg muscles using a powerjump Duration of Fright (DF) series TKK 5114, and to measure abdominal muscle kekutan using crunches. The results showed that there was a significant effect of weight training using serial and parallel methods in improving the power and strength of leg muscles, back muscles, abdominal muscles